Eksistensi Hak Anak Perempuan dalam Pewarisan Rumah: Studi Kasus di Desa Panreng - Muh. Ahsan (LPPM STAI Muhammadiyah Probolinggo, 2025)
Islamic law establishes a 2:1 inheritance ratio between sons and daughters. However, in Desa Panreng, Kecamatan Baranti, Kabupaten Sidenreng Rappang, local customs take a different approach. In this community, daughters receive the family home, land, and its contents as a special portion of the inheritance. This practice suggests that daughters may inherit a larger share than what is prescribed in Islamic law.This study aims to explore the reality behind this inheritance distribution, particularly within the Bugis community of Desa Panreng, which grants daughters a privileged inheritance. Using a qualitative research method with a sociological approach, the study gathers data through observations, interviews with community leaders, and documentation.The findings reveal that the inheritance of the house, land, and its contents is indeed granted to daughters for specific reasons one of the most significant being their role in caring for their parents in old age. This inheritance practice is deeply rooted in longstanding customs passed down through generations and is based on family consensus. The distribution of inheritance is often arranged before the passing of the parents to prevent conflicts.Ultimately, this study highlights that the inheritance system in Desa Panreng prioritizes fairness based on a child’s contribution to parental care rather than strictly following the standard principles of Islamic inheritance law. Keywords: Inheritance; Daughters; Customary Law; Bugis Ethnic Group; Sociology of Law.